Exploring knowledge and perceptions of Advanced Driver Assistance Systems (ADAS): Results of a southern Italian survey - Salvatore Leonardi; Natalia Distefano (Transportation Research Interdisciplinary Perspectives)
The evolutionary process leading to fully autonomous driving is based on ADAS (Advanced Driver Assistance Systems), which have become increasingly widespread in recent years and are the subject of a legislative regulatory process at the European level that will gradually make many of these systems mandatory for new generation vehicles. This study presents a survey aimed at investigating the propensity of a significant sample of users in southern Italy toward new technologies that will bring autonomous and cooperative vehicles to roads around the world in the not-too-distant future. The study was carried out in two phases: 1) general analysis; 2) in-depth analysis. In the first, the data obtained from the survey were analyzed to assess the level of knowledge and importance of a number of specific ADAS items in the questionnaire used. However, in the in-depth analysis, the statistical technique of path analysis was used to derive observations related to the respondent users’ level of knowledge about ADAS in general and the importance they attach to these devices for improving road safety. Considering the technological evolution toward autonomous and cooperative driving and the obligations imposed by current regulations for the design and approval of new vehicles, the results of this study raise strong doubts as to whether the context analyzed, which is probably more representative of the deep south of Europe than of Italy as a whole, is really capable of managing this important development process without trauma. Finally, this study underlines the need to promote, in the studied context and in similar contexts, different actions and strategies to improve the knowledge about ADAS and the awareness of their importance for the safety of road users.